Algebra 1

Published by Prentice Hall
ISBN 10: 0133500403
ISBN 13: 978-0-13350-040-0

Chapter 10 - Radical Expressions and Equations - Cumulative Test Prep - Gridded Response - Page 648: 16



Work Step by Step

$-a/4= -3*(a-2)/6$ $-a*1.5/4*1.5=-3*(a-2)/6$ $-1.5a/6=-3*(a-2)/6$ $-1.5a=-3*(a-2)$ $2*(-1.5a=-3*(a-2))$ $-3a=-6*(a-2)$ $-3a=-6a+12$ $3a=12$ $3a/3=12/3$ $a=4$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.